2016
DOI: 10.1111/ane.12673
|View full text |Cite
|
Sign up to set email alerts
|

Coping with multiple sclerosis-the role of social support

Abstract: Differences in coping behavior could be observed for different levels of impairment through MS. Patients tackle more intensively and more actively with their disease when trying to adapt to increasing disability with an EDSS range between 3.0 and 6.0. In addition, the coping behavior of patients with MS was connected to social support, especially support by family, friends, or other patients with MS. Results refer to the importance of special trainings to enhance coping abilities of patients with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 25 publications
1
40
0
1
Order By: Relevance
“…Another study found that degree of impairment among MS patients was related to the amount of social support they needed for coping and that special training was necessary to enhance this coping strategy (Rommer, Suhnel, Konig, & Zettl, 2016). We could find no other theory-/modelbased program for intervening in MS patients.…”
Section: Lazarus and Folkman's Transactional Model Of Stress And Copingmentioning
confidence: 89%
See 1 more Smart Citation
“…Another study found that degree of impairment among MS patients was related to the amount of social support they needed for coping and that special training was necessary to enhance this coping strategy (Rommer, Suhnel, Konig, & Zettl, 2016). We could find no other theory-/modelbased program for intervening in MS patients.…”
Section: Lazarus and Folkman's Transactional Model Of Stress And Copingmentioning
confidence: 89%
“…Schwartz in a randomized controlled trial found that quality of life was improved more by education in coping skills than was found for a peer support group (Schwartz, 1999). Another study found that degree of impairment among MS patients was related to the amount of social support they needed for coping and that special training was necessary to enhance this coping strategy (Rommer, Suhnel, Konig, & Zettl, 2016). We could find no other theory‐/model‐based program for intervening in MS patients.…”
Section: Introductionmentioning
confidence: 99%
“…They seem to be influenced by the level of impairment. Especially, moderate affected patients are tackling more intensively with their disease in comparison with less or more severe impaired patients . One way of coping is to look for other and/or additional forms of treatment: the so‐called complementary and alternative medicine (CAM) .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that there is a direct relationship between an increase in the quality of life of patients with MS and social support. The latter produces a protective effect in the lives of patients (1,2,3,4,5,6,7).…”
Section: Introductionmentioning
confidence: 99%